Surface nitriding strengthening method for strong nitride forming element high-entropy alloy
By regulating the temperature gradient and solidification rate of high-entropy alloys and combining ionic nitriding treatment, the problem of insufficient hardness after nitriding on the surface of high-entropy alloys is solved, and the hardness, strain and stress are greatly improved, and the service performance of the material is improved.
Patent Information
- Application Number
- CN202411446988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the hardness of the surface nitriding of high-entropy alloys still needs to be improved, and the combination of nitrogen and high-entropy alloys have a complex impact on performance.
By regulating the temperature gradient (G) and solidification rate (R) during the synthesis process, combined with subsequent ion nitriding treatment, the structural morphology and scale of the high-entropy alloy of the strong nitride forming element are regulated, thereby improving its mechanical properties and service performance .
The hardness of the high-entropy alloy with strong nitride forming element has been increased to at least 1000HV, the engineering strain and stress are increased, and the corrosion current density is reduced, achieving the purpose of efficient strengthening.
Smart Images

Figure CN119426600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy surface nitriding treatment, and in particular to a surface nitriding strengthening method for a high entropy alloy of a strong nitride-forming element. Background Art
[0002] Ion nitriding is a method of introducing nitrogen into the surface of metal materials by glow discharge technology, and then diffusing nitrogen into the metal materials for surface modification. After nitriding, the metal material can obtain a nitrided layer with higher hardness and higher wear resistance. It is the most economical and effective method to improve the hardness, wear resistance and fatigue resistance of metal materials.
[0003] High entropy alloy (HEA) is an alloy composed of 5 or more elements with atomic fractions between 5% and 35%. It is widely used in aviation, aerospace, machinery and other fields. HEA exhibits hysteresis diffusion effect in kinetics, lattice distortion effect in structure, "cocktail" effect in performance, and high entropy effect in thermodynamics. Therefore, HEA has the characteristics of stable structure, good ductility and corrosion resistance. At present, studies have shown that nitriding will increase the hardness of cast high entropy alloys, but the combination of nitrogen and high entropy alloys and the effect of the combination on their properties are complex.
[0004] Elements such as Al, Cr, Fe, Ti, Zr, V, Co, and Ni are known as strong nitride forming elements. Fe with a large number of valence electrons can promote the formation of FCC phases, while Al, Cr, Ti, and V with a small number of valence electrons can promote the formation of BCC phases. The addition of Zr can significantly refine the microstructure of HEA, which is a typical dendrite structure. Different crystal structures have different solid solubility for N atoms. For example, compared with BCC, the lattice parameter of FCC phase is larger and can accommodate more N atoms, so it is more conducive to the diffusion of N atoms and the formation of nitrides. The differences in crystal structure and elements lead to large differences in the nitride formation state and organizational structure obtained after HEA nitriding, which in turn affects the mechanical properties and service performance of HEA after nitriding. CN116752082A discloses a method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy, which changes the formation state and organizational structure of the high-entropy alloy, introduces a eutectic high-entropy alloy, and improves the surface hardness and wear resistance of the eutectic high-entropy alloy by nitriding the eutectic high-entropy alloy. However, the surface hardness reaches 584 to 803 HV, and there is still room for improvement. Summary of the invention
[0005] In view of the technical problem in the prior art that the hardness of high entropy alloys after surface nitriding needs to be improved, the present invention provides a surface nitriding strengthening method for high entropy alloys of strong nitride forming elements, which improves the mechanical properties and service performance of high entropy alloys of strong nitride forming elements by regulating the temperature gradient (G) and solidification rate (R) during the synthesis process and cooperating with subsequent nitriding.
[0006] The technical solution of the present invention is as follows: A surface nitriding strengthening method for a strong nitride forming element high entropy alloy comprises mixing zero-valent raw material powders Fe, Co, Cr, Ni and Al, preparing the strong nitride forming element high entropy alloy by a vacuum hot pressing sintering method or a 3D printing method, and then performing ion nitriding; Among them, during vacuum hot pressing sintering, G×R is controlled at 4000-5500K / s, and G / R is controlled at 800-1500Ks / mm 2 ; During 3D printing, the G×R at the top of the single-pass molten pool is controlled at 7000-8000K / s, and the G / R is controlled at 200-300Ks / mm 2 , G×R in the middle of the molten pool is controlled at 2000-3000K / s, G / R is controlled at 500-1200Ks / mm 2 , G×R at the bottom of the molten pool is controlled at 300-1000K / s, G / R is controlled at 2000-3000Ks / mm 2 .
[0007] Furthermore, the zero-valent raw material powder is element powder, pre-alloyed powder or alloy powder.
[0008] Furthermore, the molar ratio of Fe, Co, Cr, Ni and Al is 1:1:1:1:0.5.
[0009] Further, the ion nitriding steps are: The high entropy alloy of strong nitride forming elements was ground and polished to Ra = 1.5μm, and then ion nitriding was carried out in a pulse plasma multi-element co-nitriding furnace after ultrasonic cleaning. The cleaned high entropy alloy of strong nitride forming elements was placed on the cathode disk of the ion nitriding equipment, vacuumed to 3Pa, and then nitrogen was filled into the furnace to make the furnace pressure reach 250Pa. The vacuuming and nitrogen filling were repeated twice, and the furnace pressure was controlled at 220Pa. The workpiece pole voltage was adjusted to 250V and maintained for 10min. Then the workpiece pole voltage was adjusted to 600V, the source voltage was adjusted to 900V, and the ammonia flow rate was adjusted to 0.5m 3 / h, ion nitriding is carried out to raise the surface temperature of the high entropy alloy of strong nitride forming elements to 550℃, and the ion nitriding time is 50h.
[0010] Furthermore, during the vacuum hot pressing sintering process, the holding time is 0.5-2h and the constant pressure is 45-60MPa.
[0011] This holding time is beneficial to reducing the average grain size of columnar crystals and cellular crystals and accelerating the subsequent nitriding process.
[0012] Furthermore, during the vacuum hot pressing sintering process, the heating rate was 8°C / min, the sintering temperature was 900°C, the holding time was 1h, and the constant pressure was 50MPa. After completion, the furnace was cooled. During the process, a high-speed camera was used to measure the change in thermal radiation intensity in real time to determine G and R in the scanning vector direction.
[0013] Furthermore, the substrate used for 3D printing is selected from at least one of 38CrMoAl, 42CrMn, and 40CrNiMo alloy steels.
[0014] Furthermore, the printing powder used in 3D printing is obtained as follows: The zero-valent raw material powders Fe, Co, Cr, Ni and Al are mixed and placed in an argon atmosphere at 1.0-1.05 atmospheres with a melting current of 200-300A and a vacuum degree of 1×10 -3 ~5×10 -3 Pa, repeatedly smelted 5-8 times, taken out 5-30 minutes after the end of smelting, to obtain a strong nitride forming element high entropy alloy ingot, processed into powder, and then screened out spherical powder with a particle size of 15-53μm and a purity of ≥99.5%.
[0015] Furthermore, the 3D printing process is a selective laser melting process, the laser power is 200-450W, the scanning speed is 600-2000mm / s, the scanning spacing is 0.05-0.09mm, the layer thickness of the powder is 0.04-0.08mm, the preset thickness of the coating is 0.5-2.5mm, the oxygen content in the chamber is controlled at 0.4%-0.8%, and the protective gas is argon.
[0016] The beneficial effects of the present invention are: The preparation of HEA is a melting and solidification process, which is mainly affected by the temperature gradient (G) and the solidification rate (R). The ratio of G / R reflects the degree of supercooling at the front of the solid / liquid interface and determines the microscopic crystal morphology. G×R characterizes the cooling rate of the solidification process and determines the scale of the microstructure. The organizational morphology and grain size of HEA have an important influence on the nitriding process. Smaller columnar crystals and cellular crystals can accelerate the nitriding process and more easily form hard phase nitrides. The present invention provides a surface nitriding strengthening method for a strong nitride forming element high entropy alloy. The morphology and scale of the strong nitride forming element high entropy alloy organization are controlled by G and R, so as to achieve the regulation of subsequent nitriding. The obtained strong nitride forming element high entropy alloy has a hardness of at least 1000HV, an engineering strain of at least 20%, a stress of at least 1260MPa, and a corrosion current density of at least 1.62×10 -6 A / cm 2 , achieving the purpose of efficiently strengthening high entropy alloys of strong nitride-forming elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 Example 1 FeCoCrNiAl 0.5 Microstructure characterization of HEA before nitriding.
[0019] Figure 2 Example 2 FeCoCrNiAl 0.5 Microstructure characterization of HEA before nitriding.
[0020] Figure 3 Example 3 FeCoCrNiAl 0.5 Microstructure characterization of HEA before nitriding.
[0021] Figure 4 Comparative Example 1 FeCoCrNiAl 0.5 Microstructure characterization of HEA before nitriding.
[0022] Figure 5 Comparative Example 2 FeCoCrNiAl 0.5 Microstructure characterization of HEA before nitriding.
[0023] Figure 6 Comparative Example 3 FeCoCrNiAl 0.5Microstructure characterization of HEA before nitriding. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] Example 1 (1) The five pre-alloyed powders of Fe, Co, Cr, Ni and Al were mixed in a molar ratio of 1:1:1:1:0.5 and placed in a graphite mold for vacuum hot pressing sintering. The heating rate during vacuum hot pressing sintering was 8°C / min, the sintering temperature was 900°C, the holding time was 1 h, and the constant pressure was 50 MPa. After completion, the furnace was cooled. During the process, a high-speed camera was used to measure the powder metallurgy FeCoCrNiAl 0.5 The heat radiation intensity of HEA changes, thereby determining G and R in the scanning vector direction, and through the control of heating rate, sintering temperature, and holding time, the G×R in the whole process is controlled at 4000-5000K / s, and the G / R is controlled at 800-1500Ks / mm 2 .
[0026] At this time, FeCoCrNiAl 0.5 The microstructure of HEA is mainly columnar crystals and cellular crystals, with an average grain size of 60 μm. Figure 1 .
[0027] (2) FeCoCrNiAl 0.5 The surface of HEA was sanded and polished to a mirror surface with Ra = 1.5 μm, and ultrasonically cleaned in anhydrous ethanol for 30 min. Then, the FeCoCrNiAl 0.5 HEA is ion nitrided to clean the FeCoCrNiAl 0.5 The HEA sample was placed on the cathode plate of the ion nitriding equipment, vacuumed to 3Pa, and nitrogen was filled into the furnace to make the furnace pressure reach 250Pa. Vacuuming and filling with nitrogen were repeated twice to reduce the possible residual oxygen in the furnace. The furnace pressure was controlled at 220Pa, and the workpiece pole voltage was adjusted to 250V and maintained for 10min. The purpose was to 0.5The HEA surface was cleaned, and then the workpiece voltage was adjusted to 600 V, the source voltage was adjusted to 900 V, and the ammonia flow rate was adjusted to 0.5 m 3 / h, ion nitriding is carried out to make FeCoCrNiAl 0.5 The surface temperature of HEA was raised to 550°C and the ion nitriding time was 50 h.
[0028] FeCoCrNiAl 0.5 After nitriding, the hardness of HEA increased to 1000 HV, the engineering strain was 20%, the stress was 1260 MPa, and the corrosion current density was reduced to 1.62×10 -6 A / cm 2 .
[0029] Example 2 (1) The five pre-alloyed powders of Fe, Co, Cr, Ni and Al were mixed in a molar ratio of 1:1:1:1:0.5 and then melted in a non-consumable vacuum arc melting furnace at 1 atm argon atmosphere with a melting current of 250 A and a vacuum degree of 4×10 -3 Pa was repeatedly smelted 8 times and taken out 30 minutes after the smelting to obtain FeCoCrNiAl 0.5 HEA ingot, FeCoCrNiAl 0.5 HEA ingots are processed into FeCoCrNiAl in a gas atomization device 0.5 HEA powder, and then screen out spherical powder with a particle size of 15-53μm and a purity of ≥99.5% as the powder used for 3D printing.
[0030] The substrate used for 3D printing is selected from 38CrMoAl. The 3D printing adopts the selective laser melting process. The laser power is 300W, the scanning speed is 800mm / s, the scanning spacing is 0.06mm, the powder layer thickness is 0.05mm, the coating preset thickness is 2mm, and the oxygen content in the chamber is 0.5%.
[0031] Real-time measurement of 3D printed FeCoCrNiAl with high-speed camera 0.5 The intensity of thermal radiation changes during the HEA process, thereby determining the G and R in the scanning vector direction. Since the 3D printed molten pool is non-steady-state and is affected by the Maragoni heat flow, the G and R at the top, middle, and bottom of the molten pool printed in a single pass are quite different. During the entire 3D printing process, the G×R at the top of the single-pass molten pool is controlled at 7000-8000K / s, and the G / R is controlled at 200-300Ks / mm by controlling the laser power, scanning speed, and scanning spacing. 2 , G×R in the middle of the molten pool is controlled at 2000-3000K / s, G / R is controlled at 500-1200Ks / mm 2, G×R at the bottom of the molten pool is controlled at 300-1000K / s, G / R is controlled at 2000-3000Ks / mm 2 .
[0032] Since 3D printing relies on the superposition of countless tiny molten pools, heat is conducted from the melt to the forming layer, so the heat conduction direction determines that most of the organization in the coating cross-section area is columnar crystals and cellular crystals with directional solidification. Among them, smaller columnar crystals and cellular crystals can accelerate the subsequent nitriding process and more easily form hard phase nitrides, thereby achieving the regulation of subsequent nitriding.
[0033] At this time, FeCoCrNiAl 0.5 The top, middle and bottom parts of HEA are mainly columnar crystals and cellular crystals, with an average grain size of 30 μm. Figure 2 .
[0034] (2) FeCoCrNiAl 0.5 The nitriding treatment method of HEA is the same as step (2) of Example 1.
[0035] FeCoCrNiAl 0.5 After nitriding, the hardness of HEA increased to 1050 HV, the engineering strain was 23%, the stress was 1300 MPa, and the corrosion current density was reduced to 1.5×10 -6 A / cm 2 .
[0036] Example 3 The preparation method is the same as that of Example 1, except that the heating rate of vacuum hot pressing sintering is 9°C / min, and during the whole process, G×R is controlled at 4000-5500K / s, and G / R is controlled at 800-1300Ks / mm 2 .
[0037] After step (1) is completed, FeCoCrNiAl 0.5 The microstructure of HEA is mainly columnar crystals and cellular crystals, with an average grain size of 50 μm. Figure 3 .
[0038] After step (2) is completed, its hardness increases to 1030 HV, the engineering strain is 21%, the stress is 1280 MPa, and the corrosion current density is reduced to 1.54×10 -6 A / cm 2 .
[0039] Comparative Example 1 The preparation method is the same as that of Example 1, except that the heating rate of vacuum hot pressing sintering is 4°C / min, the sintering temperature is 700°C, and during the whole process, G×R is controlled at 1000-2000K / s, and G / R is controlled at 3000-4500Ks / mm 2 .
[0040] After step (1) is completed, FeCoCrNiAl 0.5 The microstructure of HEA is mainly columnar crystals and cellular crystals, with an average grain size of 100 μm. Figure 4 .
[0041] After step (2) is completed, its hardness increases to 700 HV, the engineering strain is 23%, the stress is 920 MPa, and the corrosion current density is reduced to 4.91×10 -6 A / cm 2 .
[0042] Comparative Example 2 The preparation method is the same as that in Example 2, except that: the laser power of 3D printing is 500W, the scanning speed is 400mm / s, and the scanning spacing is 0.1mm; during the entire 3D printing process, the G×R at the top of the single-pass molten pool is controlled at 3000-4000K / s, and the G / R is controlled at 500-800Ks / mm 2 , G×R in the middle of the molten pool is controlled at 500-1000K / s, G / R is controlled at 2000-3000Ks / mm 2 , G×R at the bottom of the molten pool is controlled at 100-300K / s, G / R is controlled at 5000-6000Ks / mm 2 .
[0043] After step (1) is completed, FeCoCrNiAl 0.5 The top, middle and bottom parts of HEA are mainly columnar crystals and dendrites, with an average grain size of 60 μm. Figure 5 .
[0044] After step (2) is completed, its hardness increases to 780 HV, the engineering strain is 24%, the stress is 940 MPa, and the corrosion current density is reduced to 4.36×10 -6 A / cm 2 .
[0045] Comparative Example 3 The preparation method is the same as that of Example 1, except that the heating rate of vacuum hot pressing sintering is 4°C / min, the sintering temperature is 850°C, the holding time is 18min, the constant pressure is 40MPa, and the G×R is controlled at 800-1800K / s and the G / R is controlled at 3000-4300Ks / mm during the whole process.2 .
[0046] After step (1) is completed, FeCoCrNiAl 0.5 The microstructure of HEA is mainly columnar crystals and cellular crystals, with an average grain size of 120 μm. Figure 6 .
[0047] After step (2) is completed, its hardness increases to 680 HV, the engineering strain is 18%, the stress is 870 MPa, and the corrosion current density is reduced to 5.13×10 -6 A / cm 2 .
[0048] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for surface nitriding strengthening of a high entropy alloy of a strong nitride-forming element, characterized in that: The zero-valent raw material powders Fe, Co, Cr, Ni, and Al are mixed, and a strong nitride-forming element high entropy alloy is prepared by a vacuum hot pressing sintering method or a 3D printing method, and then ion nitriding is performed; Among them, during vacuum hot pressing sintering, G×R is controlled at 4000-5500K / s, and G / R is controlled at 800-1500Ks / mm 2 ; During 3D printing, the G×R at the top of the single-pass molten pool is controlled at 7000-8000K / s, and the G / R is controlled at 200-300Ks / mm 2 , G×R in the middle of the molten pool is controlled at 2000-3000K / s, G / R is controlled at 500-1200Ks / mm 2 , G×R at the bottom of the molten pool is controlled at 300-1000K / s, G / R is controlled at 2000-3000Ks / mm 2 .
2. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The zero-valent raw material powder is an element powder, a pre-alloyed powder or an alloy powder.
3. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The molar ratio of Fe, Co, Cr, Ni and Al is 1:1:1:1:0.
5.
4. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The steps of ion nitriding are: The high entropy alloy of strong nitride forming elements was ground and polished to Ra = 1.5μm, and then ion nitriding was carried out in a pulse plasma multi-element co-nitriding furnace after ultrasonic cleaning. The cleaned high entropy alloy of strong nitride forming elements was placed on the cathode disk of the ion nitriding equipment, vacuumed to 3Pa, and then nitrogen was filled into the furnace to make the furnace pressure reach 250Pa. The vacuuming and nitrogen filling were repeated twice, and the furnace pressure was controlled at 220Pa. The workpiece pole voltage was adjusted to 250V and maintained for 10min. Then the workpiece pole voltage was adjusted to 600V, the source voltage was adjusted to 900V, and the ammonia flow rate was adjusted to 0.5m 3 / h, ion nitriding is carried out to raise the surface temperature of the high entropy alloy of strong nitride forming elements to 550℃, and the ion nitriding time is 50h.
5. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The holding time during vacuum hot pressing sintering is 0.5-2h and the constant pressure is 45-60MPa.
6. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: During the vacuum hot pressing sintering process, the heating rate is 8°C / min, the sintering temperature is 900°C, the holding time is 1h, and the constant pressure is 50MPa. After completion, the furnace is cooled. During the process, a high-speed camera is used to measure the change in thermal radiation intensity in real time to determine G and R in the scanning vector direction.
7. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The substrate used for 3D printing is selected from at least one of 38CrMoAl, 42CrMn, and 40CrNiMo alloy steels.
8. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The printing powder used in 3D printing is obtained as follows: The zero-valent raw material powders Fe, Co, Cr, Ni and Al are mixed and placed in an argon atmosphere at 1.0-1.05 atmospheres with a melting current of 200-300A and a vacuum degree of 1×10 -3 ~5×10 -3 Pa, repeatedly smelted 5-8 times, taken out 5-30 minutes after the end of smelting, to obtain a strong nitride forming element high entropy alloy ingot, processed into powder, and then screened out spherical powder with a particle size of 15-53μm and a purity of ≥99.5%.
9. The surface nitriding strengthening method of a high entropy alloy of a strong nitride forming element as claimed in claim 1, characterized in that: The 3D printing process is a selective laser melting process, the laser power is 200-450W, the scanning speed is 600-2000mm / s, the scanning spacing is 0.05-0.09mm, the powder layer thickness is 0.04-0.08mm, the coating preset thickness is 0.5-2.5mm, the oxygen content in the chamber is controlled at 0.4%-0.8%, and the protective gas is argon.
Citation Information
Patent Citations
Method for preparing high-hardness and high-wear-resistance nitriding layer on surface of eutectic high-entropy alloy
CN116752082A
Cited By
Low-temperature-impact-resistant high-strength bolt for high-cold railway and heat treatment method thereof
CN121428496A